2000
DOI: 10.1111/j.1550-7408.2000.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Small Subunit Ribosomal RNA Gene and Internal Transcribed Spacer Sequences Among Isolates of the Intranuclear Microsporidian Nucleospora salmonis

Abstract: Nucleospora salmonis is an intranuclear microsporidian associated with a proliferative disorder of the lymphoid cells of captive salmonid fish in the northwestern and northeastern regions of North America, in France, and in Chile. Newer diagnostic approaches have used the polymerase chain reaction (PCR) to detect the parasite in fish tissues. The target sequences for these assays lie in the small subunit ribosomal RNA (ssu rRNA) gene or internal transcribed spacer (ITS) as determined from N. salmonis from chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…E. bieneusi from the human intestine) for it to be placed in a separate genus (Docker et al 1997, Nilsen 2000. N. salmonis and the intranuclear microsporidia from Atlantic halibut are morphologically very similar, and recent studies comparing ribosomal genes suggest that the microsporidium found in halibut is most likely to be a Nucleospora species (Gresoviac et al 2000). No data concerning the mode of infection exist for the Nucleospora species from halibut.…”
Section: Microsporidiamentioning
confidence: 99%
“…E. bieneusi from the human intestine) for it to be placed in a separate genus (Docker et al 1997, Nilsen 2000. N. salmonis and the intranuclear microsporidia from Atlantic halibut are morphologically very similar, and recent studies comparing ribosomal genes suggest that the microsporidium found in halibut is most likely to be a Nucleospora species (Gresoviac et al 2000). No data concerning the mode of infection exist for the Nucleospora species from halibut.…”
Section: Microsporidiamentioning
confidence: 99%
“…Previous studies have illustrated a comparable range of sequence variability among clones produced from a single PCR reaction (<0.25%, Gresoviac et al 2000); the resemblance between N. salmonis genotypes characterised in Massif Central fish and in Atlantic salmon originating from Eastern Canada was below 0.24% of variation.…”
Section: Resultsmentioning
confidence: 99%
“…comm., Gresoviac et al 2000), is indicative of the existence of several strains, or to a lesser degree genotypes, of N. salmonis in France. The high proportion and specificity of the heterogeneous sequences described by the comparison of the rainbow trout isolate from Eastern France and the isolates from Massif Central salmonids, as well as the absence of common genetically-specific French sites, did not suggest any direct relationship between the microorganisms originating from these locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found these characteristics also in the Heterosporis anguillarum rRNA sequence. The microsporidian rRNA sequences, especially the SSU rRNA sequences, are chosen to investigate the taxonomic position and phylogeny of microsporidia species (Vossbrinck et al 1987, Visvesvara et al 1994, Baker et al 1995, Malone & McIvor 1996, Pieniazek et al 1996, Nilsen et al 1998, Gresoviac et al 2000. In this paper, we edited the reported sequence (17 revised bases) (Hung et al 1998, GenBank Accession No.…”
Section: Discussionmentioning
confidence: 99%